2018
DOI: 10.1515/ijamh-2018-0141
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of condom use among male adolescents in Indonesia

Abstract: Adolescent sexual and reproductive health problems remain a public health concern in Indonesia. An increase of premarital sex as well as early sexual debut among adolescents without any protection leads to a high risk of adverse sexual and reproductive health consequences. This study aimed to assess condom use prevalence and identify its determinants among male adolescents who are sexually active in Indonesia. This was a cross-sectional study using secondary data from the Adolescent Reproductive Health compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Our study showed that less than a quarter (26.2%) of young men do not always use condoms during sex compared to their counterparts. Our findings are consistent with those from Brazil [14] and Indonesia [16], showing low rates of condom use among young people (22.8% and 27.4%, respectively). Low and sporadic use of condoms has been linked with poor knowledge of HIV and sexual health education, which are potential risk factors for HIV transmission [13,15].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study showed that less than a quarter (26.2%) of young men do not always use condoms during sex compared to their counterparts. Our findings are consistent with those from Brazil [14] and Indonesia [16], showing low rates of condom use among young people (22.8% and 27.4%, respectively). Low and sporadic use of condoms has been linked with poor knowledge of HIV and sexual health education, which are potential risk factors for HIV transmission [13,15].…”
Section: Discussionsupporting
confidence: 92%
“…Another reason accounting for this finding could be the result of the multifaceted array of individual- and interpersonal-level influences on condom use among young people. There is evidence that unequal gender and social norms, peer influences, negative perceptions about condoms and their use, and poor youth-friendly sexual and reproductive health services have been associated with low and inconsistent condom use among young people [16,65]. However, consistent condom use has been acknowledged as one of the most fundamental preventative measures against HIV acquisition and transmission [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding why youths practice unprotected sex which puts them at high risk of HIV and other sexually transmitted infections, as well as unwanted pregnancies is vital in addressing this public health challenge (1,10). Several studies have been conducted in the Western world and Africa related to the prevalence and determinants of condom use among the youth (11,12). Some of the documented determinants of condom use among the youths include age, sex, place of residence, drug and alcohol abuse, duration of the relationship, perceived con dence to use a condom, perceived susceptibility to STIs and pregnancy, refusing to have sex if a partner refuses to use a condom, intention to bargain over the use of condoms, religion, relationship intimacy, sex-stigma and accessibility to condoms (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The protection of sex in Indonesian adolescents was at a low level. It was influenced that the socio-cultural issue that almost people assume that sexual behavior and reproductive health is something taboo and privation to discuss [8,9]. Education in adolescents has been suggested to improve knowledge  ISSN: 2252-8806 Int.…”
Section: Introductionmentioning
confidence: 99%